Foot Exercise Intervention for Diabetic Peripheral Neuropathy in Patients with Diabetes Mellitus: A Literature Review - Nuzul Fathu Rohman; Wantonoro Wantonoro; Yuli Isnaeni (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: Among individuals with type 2 diabetes mellitus, diabetic peripheral neuropathy (DPN) frequently develops as a long-term complication and substantially increases the likelihood of foot ulcer formation and lower-limb amputation. Non-pharmacological approaches, including foot exercise programs, have been proposed to improve foot function and mitigate the progression of DPN. Existing evidence suggests that foot exercises may enhance peripheral circulation, optimize foot biomechanics, and improve sensory nerve function. Objective: The present review was undertaken to critically examine and integrate recent findings regarding the impact of foot exercise interventions on patients with type 2 diabetes mellitus experiencing DPN. Method: : A systematic literature search was performed in Google Scholar, PubMed, and ScienceDirect to identify studies published within the last five years. Article selection was guided by the PICOS framework. Experimental and quasi-experimental studies investigating foot exercise interventions were included. Eleven eligible articles were reviewed and synthesized narratively. Result: The findings indicate that foot exercise interventions contribute to improvements in foot sensation, peripheral perfusion, sensory nerve function, balance, walking speed, gait performance, and foot biomechanics. Furthermore, these interventions may decrease the likelihood of diabetic foot ulcer formation. Conclusion: As a non-pharmacological intervention, foot exercise offers a practical and effective option for improving outcomes in individuals with DPN. Future research employing randomized controlled trial designs and longer follow-up periods is recommended to establish the most effective exercise protocol.